FRENULECTOMY OF SHORT FRENULUMS OF THE UPPER LIP IN THE TREATMENT OF DIASTEMAS IN CHILDREN - Sh.Y, Zokirova; Sh.I, Аnvarovа; Sh.F., Shoabdullayeva (Journal of Medical Genetics and Clinical Biology, 2024)
Objective: This study examines the relevance and necessity of addressing upper lip frenulum abnormalities in pediatric patients, given the increasing incidence due to environmental factors, dietary additives, and structural predispositions affecting periodontal health. Methods: Clinical studies and literature systematizations were reviewed to classify frenulum abnormalities and evaluate frenuloplasty techniques. Notable classifications include the morphological and attachment-based categorization by Nenashev and Kulikov and the density differentiation by Obraztsov and Larionov. Methods from Khoroshilkina, particularly the Limberg and Popovich techniques, are discussed for their effectiveness in managing frenulum-related diastemas. Results: The study highlights the efficacy of these frenuloplasty techniques, which involve either triangular flap repositioning (Limberg) or frenulum edge relocation to the transitional fold (Popovich). These methods have been demonstrated to effectively prevent and manage dentoalveolar deformities in outpatient settings. Novelty: This research underscores the need for an algorithm to guide treatment selection and optimize surgical outcomes based on individual frenulum morphology and attachment. Implications: The findings inform pediatric surgical dentistry, suggesting a structured approach to frenulum treatment to prevent progressive periodontal issues, speech impediments, and developmental irregularities in the dentofacial system. Further research should explore standardized protocols for surgical intervention selection in pediatric patients.